(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2023)
Background: Following cardiac damage, a complex process known as left ventricular adverse remodelling occurs, which is characterized by alterations in the left ventricle (LV)’s structure, form, and function. The study aims at assessing the significance of the LV sphericity index in quantifying LV geometric alterations, as well as the conicity index’s significance in recognizing regional variations in LV geometry and evaluating its relation to the heart’s systolic and diastolic function. Methods and Methods: A total of 50 individuals with anterior myocardial infarction (MI) participates in this cross-sectional study. Sphericity (SI) and conicity indices (CI) are calculated using the ratios of the short axis and long axis, and the apical to short LV axis, respectively. Then measurements of the LV’s systolic and diastolic functioning are done. Results: The sphericity index and systolic parameters display a statistically significant negative correlation (P<0.05). The conicity index and systolic parameters show a statistically non-significant negative correlation (P>0.05). The relation between CI and SI with LV diastolic parameters reveal a positive correlation, but it was statistically non-significant (p>0.05). Only the left atrial volume index (LAVI) was statistically significant with SI (p<0.05). Conclusion: This study concludes that LV indices are a simple, non-invasive measure of LV remodelling, whether locally by CI or globally by SI, and can reflect the LV’s systolic and diastolic performance based on correlation studies.